Chromatographic study of sitagliptin and ertugliflozin under quality-by-design paradigm - Sunitha Gurrala; Shivaraj; Panikumar Durga Anumolu; Haripriya D; Subrahmanyam CVS (Brazilian Journal of Pharmaceutical Sciences, 2023)
Abstract The present study entails the systematic development and validation of a stability-indicating RP-HPLC method for the analysis of sitagliptin and ertugliflozin in a fixed-dose combination. Analytical quality by design (AQbD) concepts were used to define critical method variables, employing Pareto risk assessment and a Placket-Burman screening design, preceded by a Box-Behnken design with response surface analysis to optimise critical method parameters such as % acetonitrile (X1), buffer pH (X2) and column oven temperature (X3). Multiple response optimisation (Derringer’s desirability) of variables was accomplished by studying critical analytical attributes, such as resolution, retention time and theoretical plates. The title analytes were separated effectively on a PRONTOSIL C18 column at 37 °C using a mobile phase of acetonitrile:acetate buffer, pH 4.4 (36:64 percent v/v), pumped at a flow rate of 1 mL/min, and UV detection at 225 nm. Linearity was observed over a concentration range of 25-150 µg/mL and 3.75-22.5 µg/mL at retention times of 2.82 and 3.92 min for sitagliptin and ertugliflozin, respectively. The method obeyed all validation parameters of the ICH Q2(R1) guidelines. The proposed robust method allows the study of the selected drugs in pharmaceutical dosage forms as well as in drug stability studies under various stress conditions.